THE EFFECT OF COOPERATIVELEARNING MODEL WITH STUDENT TEAM ACHIEVEMENT DIVISION TYPE AND MOTIVATION TOWARD PHYSICS STUDY RESULT - Nadrah Nadrah (Green Publisher, 2022)
The research aimed to describe the effect of cooperative learning model with Student Team Achievement Division type and motivation on study results in physics. This is a true-experimental design’s research with a 2 × 2 factorial design conducted at SMAN 2 Makassar. Independent variable is the model of learning; which they are cooperative learning model STAD (Student Team Achievement Division) and conventional learning model. Motivation as moderator variable was divided into two factors, namely high and low learning motivation. The dependent variable is the study result of learning physics. The instrument was a questionnaire of motivation to learn physics is used to measure the motivation of students, whereas physics achievement test used to measure the study results of physics in students. There are 36 students of class X in SMAN 2 Makassar taken using random sampling techniques as samples. The data analyzed using analysis of variance two-lane. The results showed (1) Study results of physic in students taught using cooperative learning model STAD (Student Team Achievement Division) higher than students taught using conventional learning models. (2) Students with high motivation to learn physic, the study results of studying physics taught using cooperative learning model STAD (Student Team Achievement Division) higher than students taught by conventional learning model; (3) Students with low motivation to learn physics, study results of physics taught using cooperative learning model STAD (Student Team Achievement Division) lower than students taught by conventional learning model, and (4) there was a significant interaction effect between learning model and motivation for study results in physics